Global health impacts of nanotechnology law: Advances in safernano regulation. (2022) - Feitshans, Ilise L; Sabatier, Philippe
Abstract: Nanoregulation is a dynamic process worldwide. This article begins with a short overview of legislative antecedents for emerging laws about nanotechnology, then examines key trends in emerging nanoregulations that govern global commercialization of nanomaterials. Around the world, hundreds of emerging laws have begun to sprout like mushrooms in unexpected places all over the globe. Surrounding these mushrooms is a treacherous swamp of new law, draft laws and pre-existing laws. Although guidelines based on expertise can sometimes serve as powerful influencers of opinion and may determine subsequent course of actions, such pronouncements lack the legitimate power of statutory law. This article begins with a short overview of legislative antecedents for emerging laws and guidelines about nanotechnology, then examines key trends in emerging nanoregulations that govern global commercialization of nanomaterials. Science and law can partner to minimize risk while maximizing societal benefit; research scientists and others can participate proactively in that legislative process.